The Geotourism Product—What It Is and What It Is Not - Ľubomír Štrba; Silvia Bodzáš Palgutová; Ján Derco; Branislav Kršák; Csaba Sidor (Geosciences, 2025)
The worldwide expansion of geotourism and its ongoing development have captured the interest of numerous scholars, prompting them to investigate various theoretical dimensions within this emerging field. This paper explores the concept of geotourism products and the importance of comprehensively understanding this topic. A thorough review of the existing literature indicates that different researchers offer diverse definitions and interpretations of geotourism products. However, analysis of relevant publications reveals that these perspectives do not adequately incorporate the fundamental principles of geotourism alongside the well-defined and broadly accepted concept of tourism products in general. To facilitate the accurate analysis of research outcomes and to support the effective advancement of geotourism, this paper advocates for a clear and well-defined understanding of what constitutes a geotourism product.